2022
DOI: 10.3390/rs14071617
|View full text |Cite
|
Sign up to set email alerts
|

An Estimation Method for PM2.5 Based on Aerosol Optical Depth Obtained from Remote Sensing Image Processing and Meteorological Factors

Abstract: Understanding the spatiotemporal variations in the mass concentrations of particulate matter ≤2.5 µm (PM2.5) in size is important for controlling environmental pollution. Currently, ground measurement points of PM2.5 in China are relatively discrete, thereby limiting spatial coverage. Aerosol optical depth (AOD) data obtained from satellite remote sensing provide insights into spatiotemporal distributions for regional pollution sources. In this study, data from the Multi-Angle Implementation of Atmospheric Cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Determination of the training function: the training functions include the traingd, traingdm, and trainlm algorithms. The trainlm algorithm is the fastest backpropagation algorithm in the MATLAB toolbox 40 . Therefore, trainlm was selected as the network training function in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Determination of the training function: the training functions include the traingd, traingdm, and trainlm algorithms. The trainlm algorithm is the fastest backpropagation algorithm in the MATLAB toolbox 40 . Therefore, trainlm was selected as the network training function in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The trainlm algorithm is the fastest backpropagation algorithm in the MATLAB toolbox. 40 Therefore, trainlm was selected as the network training function in this study. 3.…”
Section: Bpnn Modelmentioning
confidence: 99%
“…Li et al [ 13 ] estimated the seasonal spatial distribution of PM 2.5 in Beijing using MCD19A2 data, and the results show that MCD19A2 data have a strong ability to predict the ground PM 2.5 level on a seasonal scale basis. Gu et al [ 14 ] determined the daily concentration of PM 2.5 in Dalian using MCD19A2 data and found that the spatial distribution of AOD and PM 2.5 tended to be consistent, and the PM 2.5 value in industrial areas was high. The above research shows that MCD19A2 is feasible in PM 2.5 inversion.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous studies retrieved the aerosol optical depth (AOD) from satellite remote sensing imageries (e.g., moderate resolution imaging spectroradiometer (MODIS) and ozone monitoring instrument (OMI)) to estimate the PM 2.5 concentrations [4,9,[14][15][16][17][18]. These AOD products with resolution of 1-17.6 km could reveal the overall distribution of PM 2.5 concentrations within an area.…”
Section: Introductionmentioning
confidence: 99%